A temporal analysis of how entrepreneurial goal intentions, positive fantasies, and action planning affect starting a new venture and when the effects wear off - Gielnik, Michael M.; Barabas, Stefanie; Frese, Michael; Namatovu-Dawa, Rebecca; Scholz, Florian A.; Metzger, Juliane R.; Walter, Thomas (Journal of Business Venturing, 2014)
The road from intentions to actions and new venture creation is long. So far, the literature has provided insights into action-regulatory factors that contribute to new venture creation. However, the literature has neglected to take into account the temporal dynamics underlying these relationships. We contribute to action-regulation theories in entrepreneurship by theorizing about and investigating how the effects of action-regulatory factors hold over time. We hypothesize that the action-regulatory factors of entrepreneurial goal intentions, positive fantasies, and action planning have combined effects on new venture creation. Furthermore, we hypothesize that these effects become weaker over time. To test our hypotheses, we studied 96 Ugandan entrepreneurs over 30months. Our results supported our hypotheses. Action planning moderated the effects of entrepreneurial goal intentions and positive fantasies on new venture creation. Furthermore, the effects were significant in the beginning and wore off over time. Our study shows that including a time frame in theoretical models is important to derive valid conclusions from empirical results and to develop more precise theories.